Leibniz and the issue of subjectivity - Bonneau, Cristiano (Argumentos - Revista de Filosofia, 2010)
The reasoning of the monadic universe carries important consequences for think about a theory of subjectivity in the philosophy of Leibniz. In describing the monad, the German philosopher explains its attributes and safeguards two fundamental concepts: autonomy and perspective. This article is to explain the philosophy of Leibniz assumptions guaranteeing a notion of the individual, based on the principle of identity and fully representative of the world from itself (speculum vitale). Thus, the controversy Renaut-Heidegger is the starting point to think of a plan of subjectivity in Leibniz.